Evaluation of antimicrobial efficacy of antibiotics and calcium hydroxide against enterococcus faecalis biofilm in dentine - Chai, W.L; Hamimah, H; Hamimah, M (Universiti Kebangsaan Malaysia, 2013)
The objective of this study was to investigate the antimicrobial efficacy of erythromycin, oxytetracycline and calcium hydroxide [Ca(OH)2] against Enterococcus faecalis biofilm in dentine. E. faecalis ATCC 29212 (American type culture collection) was inoculated into standard tooth sections and incubated in aerobic atmosphere at 37°C for 21 days. The infected tooth sections were then exposed to the test agents for 5 and 10 min. The colony forming units (CFU) after the exposure periods at three different depths <100 μm, 100-350 μm and 350-500 μm were enumerated. After 5 min of exposure, both antibiotics had significantly lower CFU count than Ca(OH)2 solution at three dentinal depths. Comparing with the oxytetracycline, the CFU count of the erythromycin was significantly (p<0.05) lower at the depth of 100-500 μm. Similarly, after 10 min of exposure, erythromycin had significantly lower CFU count (p<0.05) at three dentinal depths. Oxytetracycline showed significantly lower CFU count than Ca(OH)2 at 100 μm depth. Comparing with the two exposure times, the erythromycin and Ca(OH)2 groups showed significant lower CFU counts after 10 min of exposure in the antimicrobial agents to 5 min. In conclusion, both antibiotics show better antimicrobial activity than Ca(OH)2 in removing the E. faecalis biofilm in dentine.